Implementation of industrial process control in Johore industrial area - 380934 Kavitha Kandasamy (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2001